The latitudinal tilts of wealth and education in Peru: Testing them, explaining them, and reflecting on them - León, Federico R. (2012)
Comparisons between countries around the globe reported since 1999 reveal that nations’ wealth consistently increases with distance from the Equator. Is Peru’s territory exempt from this trend? This study used GPS coordinates, questionnaire data, climate files, and census information from the 2000 Peru Demographic and Health Survey, Climate Wizard, and G-Econ data sets toreconcile the contradictory national evidence and understand the role of certain geophysical and social variables. Household assets increase from north to south in the Brack ecological regionswith latitudinal orientation which were studied (Desert, Puna, Yunga, Amazon), especially in rural settings, and as does women’s education, except in the Amazon. Neither temperature nor fourteen other geophysical and social variables account for such effects, though women’s domestic power explains them in the Yunga ecoregion. The findings can be understood through two theoretical perspectives: one, according to the evolutionary theses of Lynn, Rushton, and Kanazawa, suggests the genetic fixation of differential intellectual levels caused by an ancestral adaptation of Peruvian to various conditions of climate and altitude. The other, combining what is known about ultraviolet radiation, vitamin D, and production of sexual hormones with Zajon’sconfluence theory, is defined by fertility rate and the consequent intellectual home environment for the child. Both predict the increment of IQ and educational PISA scores from north to south Peru, but one points toward education and the other to family planning as human development strategies.